Protective immune response in rainbow trout (Oncorhynchus mykiss) against the parasitic nematode Anisakis simplex - Kumas, Kaan; Andersen, Maja Hauptmann; Jaafar, Rzgar; Henard, Cyril; Kania, Per Walter; Buchmann, Kurt (Frontiers in Immunology, 2025)
IntroductionParasitic nematodes are prevalent in fish populations. The parasites are pathogenic but depress host responses, which limit clearance of the pathogens from the invasion sites. We hypothesized that one of several control strategies, which could augment protection, is immunization of the fish host with parasite antigens prior to live pathogen exposure.MethodsWe used rainbow trout Oncorhynchus mykiss as a host model and third stage larvae (L3) Anisakis simplex (Nematoda, Ascaridoidea, Anisakidae) as pathogen model. We used a total of 120 fish and immunized 40 of the fish with a homogenate (adjuvanted) of parasite larvae (i.p. injection), 40 fish received adjuvant only and 40 PBS. Following 38 days (d) half of the fish in each group were exposed to infection with live worms (oral administration), and after an additional 25 d the infection success was evaluated together with antibody responses in the different groups.ResultsInjection of A. simplex L3 antigens induced a series of adaptive and innate host responses. ELISA and Western blot analyses indicated specific IgM reactions in immunized trout against worm antigens with molecular weights (MW) of approximately 39, 103 and 119 kilodalton (kDa). Fish immunized and subsequently infected with live larvae reacted to those three and six additional antigens with MW approximately 61, 73, 84, 152, 186 and 277 kDa. The immunized fish showed a significantly lower worm burden following exposure to live parasite larvae (when compared to naïve fish), but no full protection was achieved. Expression analyses of both adaptive and innate immune genes in fish showed a general down-regulation following infection.DiscussionPrior immunization with A. simplex L3 homogenate induced a strong antibody response, but the protection was incomplete. It was noteworthy that an infection period (25 d) with live parasites merely induced an insignificant antibody response. It may be explained by the immunosuppressive compounds released by live worm larvae. With the aim of increasing the protective response, we suggest in future immunization experiments to target immunosuppressive worm antigens by immunizing the host organisms with excretory/secretory (ES) proteins and extracellular particles from A. simplex L3.